Shape and size variations of Aegla uruguayana (Anomura, Aeglidae) under laboratory conditions: A geometric morphometric approach to the growth - Diawol, Valeria Paola (2015)
Crustacean growth studies typically use modal analysis rather than focusing on the growth of individuals. In the present work, we use geometric morphometrics to determine how organism shape and size varies during the life of the freshwater crab, Aegla uruguayana Schmitt, 1942. A total of 66 individuals from diverse life cycle stages were examined daily and each exuvia was recorded. Digital images of the dorsal region of the cephalothorax were obtained for each exuvia and were subsequently used to record landmark confgurations. Moult increment and intermoult period were estimated for each crab. Differences in shape between crabs of different sizes (allometry) and sexes (sexual dimorphism; SD) were observed. Allometry was registered among specimens; however, SD was not statistically signifcant between crabs of a given size. The intermoult period increased as size increased, but the moult frequency was similar between the sexes. Regarding ontogeny, juveniles had short and blunt rostrum, robust forehead region, and narrow cephalothorax. Unlike juveniles crabs, adults presented a well-defned anterior and posterior cephalothorax region. The rostrum was long and stylised and the forehead narrow. Geometric morphometric methods were highly effective for the analysis of aeglid-individual- growth and avoided excessive handling of individuals through exuvia analysis.